2019
DOI: 10.1016/j.earscirev.2019.01.018
|View full text |Cite
|
Sign up to set email alerts
|

New starting point for the Indian Ocean: Second phase of breakup for Gondwana

Abstract: The amalgamation of Gondwana and its subsequent fragmentation has been a subject of several studies over the past five decades, yet the very important question of the initial geometry of the supercontinent remains enigmatic. Current reconstruction models of the Indian Ocean are characterized by large gaps, overlaps and misfits of major structural and Cratonic bodies in their fit, and positions of tectonic blocks that are inconsistent with field observations, a phenomenon sustained by inadequate data, long stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(85 citation statements)
references
References 129 publications
6
73
0
Order By: Relevance
“…The MCP, East of the Lebombo monocline, exhibits low crustal velocities, from 1‐D shear wave velocity profiles (Domingues et al, ) inconsistent with the presence of an oceanic crust as suggested by most of the recent models of Gondwana reconstruction (Figure b). Finally, the new kinematic fit proposed by Thompson et al () supports the same conclusions.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…The MCP, East of the Lebombo monocline, exhibits low crustal velocities, from 1‐D shear wave velocity profiles (Domingues et al, ) inconsistent with the presence of an oceanic crust as suggested by most of the recent models of Gondwana reconstruction (Figure b). Finally, the new kinematic fit proposed by Thompson et al () supports the same conclusions.…”
Section: Introductionsupporting
confidence: 71%
“…Therefore, all propositions, interpretations and conceptual models must be restored on precise palaeo‐geographic maps to test their consequences on the global view and be validated or falsified (Aslanian & Moulin, ). Symmetrically, palaeo‐geographic reconstructions should take into account all observations available on passive margins and continental deformation to avoid gaps and overlaps (Moulin, Aslanian, & Unternehr, ; Thompson, Moulin, Aslanian, Clarens, & Guillocheau, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations